Anti-Candida albicans activity of thiazolylhydrazone derivatives in invertebrate and murine models - Cruz, Lana Ivone Barreto (2018)
Candidiasis is an opportunistic fungal infection with Candida albicans being the most frequently isolated species. Treatment of these infections is challenging due to resistance that can develop during therapy, and the limited number of available antifungal compounds. Given this situation, the aim of this study was to evaluate the antifungal activity of four thiazolylhydrazone compounds against C. albicans. Thiazolylhydrazone compounds 1, 2, 3, and 4 were found to exert antifungal activity, with MICs of 0.125–16.0 µg/mL against C. albicans. The toxicity of the compounds was evaluated using human erythrocytes and yielded LC50 > 64 µg/mL. The compounds were further evaluated using the greater wax moth Galleria mellonella as an in vivo model. The compounds prolonged larval survival when tested between 5 and 15 mg/kg, performing as well as fluconazole. Compound 2 was evaluated in murine models of oral and systemic candidiasis. In the oral model, compound 2 reduced the fungal load on the mouse tongue; and in the systemic model it reduced the fungal burden found in the kidney when tested at 10 mg/kg. These results show that thiazolylhydrazones are an antifungal towards C. albicans with in vivo efficacy.